Writing effectively for English academic essays: an exploration of tertiary students’ challenges - Hairul (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2023)
This study explores EFL students’ challenges in writing an academic essay in their academic writing class. The participants of the study were ten EFL students, especially students from Bengkayang Regency, West Kalimantan, in the Academic Writing classes at the English Language Education Program, a private university in the academic year of 2020-2021. A semi-structured interview was used as the instrument of data collection to achieve the research goal. The data analysis indicated that the writing challenges were mainly related to developing writing ideas, writing sentences with correct grammar, finding references to support their writing, writing the end-text references of their paper, and understanding the feedback from their lecturer. This study concludes with some empirical evidence that students’ challenges in writing an academic essay are quite influential for their performance to produce good quality in writing an academic essay. This study hopes to provide practical ideas for teachers to help their students enhance their academic essay writing.